FORMATION AND EVALUATION OF VALUE ADDED OF INNOVATIVE PRODUCTS IN THE FIELD OF BIOMEDICINE - Varaksa, Natalia; Аlimov, Sergey; Maslov, Boris; Alimova, Maria (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The main indicator for the high rate of economic development of the country is the alignment of national advanced technologies in the global value chain.The novelty of the research study is to develop a set of indicators for assessing the value added of innovation based on the specific structure of products in the field of biomedical technologies.The aim of the research study is to summarize the scientific developments in the field of formation of value added of innovative products, to identify its specific structure in the field of biomedicine and to develop a set of indicators for its evaluation.The research uses methods of scientific search and generalization of literature, legislation, statistical analysis, monitoring, the dialectical method, analysis, synthesis, comparison, abstraction, specification.The paper reveals the specific structure of products in the field of biomedical technologies, which is based on innovative flows to bring research projects in the field of biomedicine to the final product. The proposed in the paper set of indicators for assessing the value added of innovation will form the basis for a detailed analysis of the feasibility of starting the development of an innovative product, determining the efficiency and profitability of commercialization of biomedicine products.